The Effect of Reverse Intergenerational Influence on purchase and Brand Equity of Durable Goods - Kulkarni , Swati Ashutosh (International Journal of Management Excellence (ISSN: 2292-1648), 2014)
The Intergenerational Influence (IGI) is the transmission of beliefs, perceptions, cognition, attitudes and behaviors from one generation to another. It is a fundamental mechanism by which culture is sustained over time. Its key elements are embedded within socialization theory. Reverse IGI indicates the transmission of beliefs and perception from child to parent. In this study the influences of children on their parent’s decision making for buying durable goods such as cars, mobile phones, laptops, air conditioners, and televisions have been studied. Parents are of age group between 45 and above. The questionnaire was designed and given to 50 respondents for the pilot study. Based upon the findings of the pilot study, the questionnaire was finalized and has been distributed to respondents in Mumbai area. In Preliminary results of a pilot study, respondents were asked to report on a variety of product category of durable goods and their brands. To test for (reverse) IGI, it is investigated if one party’s brand image perceptions, brand consideration, brand preference and loyalty (behavioral and attitudinal) have a significant influence on the other party’s brand awareness, image, consideration, preference and loyalty. In addition to these main effects, gender (of the child) and family communication patterns are expected to influence (reverse) IGI.